2016
DOI: 10.1108/ijcthr-07-2015-0080
|View full text |Cite
|
Sign up to set email alerts
|

The influence of destination image and tourist satisfaction on tourist loyalty: a case study of Chinese tourists in Korea

Abstract: Purpose The purpose of this paper is to explore both the cognitive and affective images and examine the effects of destination image through both aspects on satisfaction levels and tourist loyalty. Design/methodology/approach Data collection was conducted using the convenience sampling method. The on-site survey was carried out with Chinese tourists at the popular tourist sites in Seoul City. Findings The results showed that the cognitive image had a direct influence on the affective image and confirmed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
137
2
15

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(176 citation statements)
references
References 44 publications
(63 reference statements)
22
137
2
15
Order By: Relevance
“…Furthermore, the existence of tourist loyalty could also help in indirectly promoting the place to others (for example: when a tourist promoted the place to his/her peers). Previous research by Chiu et al, (2016) had found that tourist loyalty could be affected by destination image and perceived quality, either directly or indirectly through tourist satisfaction. Furthermore, previous research by Jalivand et al (2014) had found that satisfaction could mediate the relationship between perceived value and perceived quality towards loyalty.…”
Section: Research Introductionmentioning
confidence: 98%
“…Furthermore, the existence of tourist loyalty could also help in indirectly promoting the place to others (for example: when a tourist promoted the place to his/her peers). Previous research by Chiu et al, (2016) had found that tourist loyalty could be affected by destination image and perceived quality, either directly or indirectly through tourist satisfaction. Furthermore, previous research by Jalivand et al (2014) had found that satisfaction could mediate the relationship between perceived value and perceived quality towards loyalty.…”
Section: Research Introductionmentioning
confidence: 98%
“…In the services sector, especially in hospitality and tourism, customer satisfaction has become a major issue and a challenge, since the customers' attitudes, perceptions, personality, and the tolerance of ambiguity may differ from one person to another. The consumers perceive the same service in different ways, therefore, the standardization of the services are more difficult than the tangible offerings (Chiu et al, 2016).…”
Section: Tourist Satisfactionmentioning
confidence: 99%
“…Previous studies found that tourist loyalty as an outcome was affected positively by tourist satisfaction. Therefore, when customer satisfaction increases, lead to intention to return and recommend to other rises, whereby significant for customer loyalty (Amoah et al, 2016;Chiu et al, 2016;Liang, 2008;Wahyuningsih, 2012). As Kotler et al (2017) stated the customer loyalty drives to continue to use the same product or service, able to reduce cost of promotional, decreased the price sensitivity.…”
Section: Competitive Advantage Through Tourist Satisfaction and Loyaltymentioning
confidence: 99%
“… Protection from satisfied customers in a crisis situation (loyalty in crisis). Customers' experiences is the key element for competitive advantage through loyal customers [4], [7], [37], [38].  Product diversification growths through one stop shopping.…”
Section: B Antecedents To Competitive Advantage Creationmentioning
confidence: 99%